PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, PERTUMBUHAN LABA, LIKUIDITAS DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2015 - Sagita Heppy Jayanti, 12.05.52.0135; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2017)
The purpose of this study was to examine the effect of financial ratios to predict earnings quality on manufacturing companies in the Indonesian Stock Exchange using financial ratios variable which is capital structure, size of company, the growth of profit, liquidity, and investment opportunity set as independent variables. While earning quality is measured using Earnings Response coefficient (ERC) as the dependent variables. The population in this study were manufacturing companies that listed on Indonesian Stock Exchange. Samples are taken 136 manufacturing companies with purposive sampling method and observation period during five (2012-2015). Relationship and influence between variable is described by using multiple regression analysis. The result showed that capital structure hassignificant and positive effect to the earnings quality. size of company had no significant and positive effect to the earnings quality. While the growth of profit, and has significant and negative effect to the earnings quality. Liquidity had no significant and positive effect to the earnings quality. Investment Opportunity SetÂ  had significant and positive effect to the earnings quality.Keywords: Capital Structure, Size Of Company, The Growth Of Profit, Liquidity, Investment Opportunity Set and Earning Quality